(untitled) (International Journal of Studies in Nursing, 2017)
Latino adolescents in the United States are more likely to engage in early and risky sexual behavior compared to adolescents from other racial and ethnic groups. The quantity and quality of parent-adolescent sexual communication has been suggested as the best predictor on adolescent sexual behavior. Method: A systematic literature review of studies was conducted with relationships between selected parental, adolescent and cultural variables and Latino adolescents’ intentions to engage in sexual behavior, derived from the Parent-Based Expansion of the Theory of Planned Behavior (PETPB). Results: From 20 studies reviewed, only 12 reported findings specifically to Latinos living in the United States. There was consistency across these studies supporting the relationships between adolescents’ attitudes, subjective norms, and self-efficacy toward risky sexual behavior and adolescents’ intentions to have sexual intercourse and to use condoms. However, few studies examined any predictors of parent-adolescent sexual communication guided by the PETPB that included psychological factors and antecedent factors. Conclusion: Future studies should be longitudinal and should include a larger sample of Latino with more variation in levels of acculturation in order to generalize the findings to the diverse Latino immigrant population living in the United States.